Driving after alcohol consumption among residents of Northeastern Brazil: National Health Survey 2019 - Renata da Silva Gomes; Amanda Cristina de Souza Andrade; Vanessa Moraes Bezerra (Ministério da Saúde do Brasil, 2024)
ABSTRACT Objective To estimate the prevalence of factors associated with drinking and driving in Northeastern Brazil. Methods This was a cross-sectional study conducted with participants from the 2019 National Health Survey, aged ≥ 18 years; the analysis of the association between sociodemographic variables and the outcome, stratified by sex, was performed using Poisson regression. Results The prevalence of drinking and driving was 21.0% ( 95%CI 19.9;23.2), with 24.6% ( 95%CI 22.7;26.5), in males and 10.1 % ( 95%CI 7.9;12.7), in females (p-value < 0.001); among men, younger age groups (PR = 1.70 - 95%CI 1.29;2.24), higher household income (PR = 1.74 - 95%CI 1.33;2.28), rural residence (PR = 1.48 - 95%CI 1.26;1.74) and motorcycle riding (PR = 1.29 - 95%CI 1.05;1.58) were associated with the event, while no association was observed among women. Conclusion Prevalence of drinking and driving was high in the Northeast region, especially among the male population; preventive measures targeting this group and intensified enforcement are necessary.